O ensino religioso em Boa Vista - RR na perspectiva do sentido da vida : abordagem frankliana - Araújo, Jacilda Barreto de (2013)
This paper aims to examine whether the Religious Studies is contributing to the formation of teenagers in their entirety grounded in the theoretical approach frankliana comprising the human bio psychosocial affective, axiological and spiritual aspects focusing on four areas namely: meaning of life, suffering, work, love and sex. We sought to discover the feelings that teens experience in postmodernity and what they do to overcome this situation called crisis of meaning. The "how to give meaning to life" was the key to the research based on Viktor Frankl and Paulo Freire. Were made parallel theories including the various dimensions of adolescence in the context of Religious Studies from the perspective of the construction discover the meaning of life. Methodological ideas have been suggested for use in Religious Studies lessons that can contribute in the spiritual development of the student from the perspective of forming future adults capable of recognizing themselves and others.